Manipulation of magnetization and spin transport in hydrogenated graphene with THz pulses - Svaneborg, Jakob Kjærulff; Bach Lorentzen, Aleksander; Gao, Fei; Jauho, Antti-Pekka; Brandbyge, Mads (Frontiers in Physics, 2023)
Terahertz (THz) field pulses can now be applied in Scanning Tunnelling Microscopy (THz-STM) junction experiments to study time resolved dynamics. The relatively slow pulse compared to the typical electronic time-scale calls for approximations based on a time-scale separation. Here, we contrast three methods based on non-equilibrium Green's functions (NEGF): (i) the steady-state, adiabatic results, (ii) the lowest order dynamic expansion in the time-variation (DE), and (iii) the auxiliary mode (AM) propagation method without approximations in the time-variation. We consider a concrete THz-STM junction setup involving a hydrogen adsorbate on graphene where the localized spin polarization can be manipulated on/off by a local field from the tip electrode and/or a back-gate affecting the in-plane transport. We use steady-state NEGF combined with Density Functional Theory (DFT-NEGF) to obtain a Hubbard model for the study of the junction dynamics. Solving the Hubbard model in a mean-field approximation, we find that near-adiabatic first order DE provides a good description for STM voltage pulses up to the 1 Volt range.